Editorial - González-Campo, Carlos Hernán (Cuadernos de Administración, 2019)
This issue becomes a new opportunity for the national and international scientific community to judge the outcome of each of these proposals. In 2019, we will be celebrating 43 years of publishing and hope that you will continue to accompany us as readers and collaborators of our scientific journal “Cuadernos de Administración”. The content of each of these eight articles is the sole responsibility of their authors. In this issue, the first article is entitled “Critical Success Factors in Implementing IT in MSMEs”, presents the results of a quantitative study that sought to determine the critical success factors that influence the level of implementation of information technologies within micro and small businesses in the region of northeastern Mexico. “Knowledge management from the organizational culture in call centers in Manizales”, is the title of the second article, which shows the results of a descriptive and correlational qualitative research on knowledge management in BPO companies in the city of Manizales, Colombia. The third article “Cultural hybridization in three Colombian indigenous productive organizations” is a qualitative research in three IPOs of the Nasa ethnic group in Colombia; in the end, it presents the results and conclusions of the research process and also some limits of thereto. “Mud, value and welfare. An economic estimation of the impact in the Anchicayá river basin”, is the fourth article in this issue of the journal Cuadernos de Administración; its authors present their economic assessment of the environmental impact in projects implemented in territories of the Colombian Pacific Coast. The fifth article is called “Effect of trading on the profitability and solvency of Colombian banks”, which discusses the business models adopted by Colombian banking. With the analysis of data panel, they study the effect of diversification of Colombian commercial banks’ revenues on profitability and financial solvency, between 2005 and 2014. “Real Returns of Private Pension Funds in Colombia” is the title of the sixth article, related to the performance of the private pension system in Colombia, Individual Benefit Plans Covered by Pooled Contributions, where the returns generated by daily transactions of pension funds from 1995 to December 2016 are analyzed from a database. The authors use the methodology established by the Financial Superintendence of Colombia (SFC) to calculate returns, determining the net profitability of explicit administration costs that the affiliate must bear and adjustment for inflation. The following article is the result of a literature review related to family businesses and socio-emotional wealth, entitled “Diversification of the family business in emerging countries from the perspective of socio-emotional wealth”. The authors identify the relevant aspects studied in relation to the diversification of the family business. The reflection is aimed at establishing the influence that family objectives exert on business decision-making. “The instruments of public policy. A transdisciplinary look”, is the title of the last article in this issue. The authors present the systematization of public policy instruments, disciplines such as public law, public sector economics and political science, especially public policy. The publication of the number 63 of Cuadernos de Administración by the Faculty of Administration Sciences of the Universidad del Valle, allows us to continue consolidating ourselves as a means of disseminating scientific knowledge in our field. Since the first issue in 1976, we have tried to publish, on a continuous basis, different types of scientific research articles, of review or reflection, by national and international authors who have relied on us to spread their knowledge. To each and every one of them, to our authors, to our arbitrators, to the members of the Editorial and Scientific Committees, but especially to you, our readers, we want to thank you for allowing us to continue generating through digitization a greater impact on the sciences of administration.